Dampak Penggunaan Konten Youtube terhadap Minat Belajar Bahasa Inggris Mahasiswa Universitas Pamulang - Juitania Juitania; I Gede Adi Indrawan (Universitas Indraprasta PGRI Jakarta, 2020)
Students often face many problems in learning process; one of the problem is attentiveness of learning. Students’ attention is relatively low when they face difficult subject, such as English. Student attentiveness can be formed by interesting learning media. The more interesting learning media used, the more interested students will be learnt. YouTube is social media that is often used as learning media. The Video tutorials containing various learning topics are widely uploaded on YouTube and the contents are attracted by the public. The English learning video is one of the learning video found on YouTube, which can be accessed by all levels of society, including students. The purpose of this research is to find out and analyze the effect of using YouTube content as teaching media toward students’ attentiveness in learning English in Bachelor Degree of Accounting Program in Pamulang University. Descriptive statistics and causality were the method of the research. Quantitative research in looking at variable relationships to the more researched object is the cause and effect (causal), Therefore, in the research, there are independent variable and dependent variable. The result shows the use of YouTube content as teaching media has a positive and significant influence on learning English in undergraduate student of Bachelor Degree of Accounting Program in Pamulang University.